Analisis Profitabilitas dalam Kinerja Keuangan dan Ukuran terhadap Nilai Perusahaan di PT. IBU (Indo Beras Unggul) - Muhammad Fikri Haikal; Hananda Faisa Putri; Nadia Zahratunisa; Delima Pebrianti Salsabila; Pradipta Rizky Ferdian; Nurlaela Fitriyani; Melia Kusnadi; Lanny Evita Tandayu; Alimah Yuliastuti; Mutia Angraeni; Wanda Ragilita Azzahro (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze how profitability in financial performance and company size affect company value, with a case study on PT. Indo Beras Unggul (PT. IBU). Profitability is an important indicator in measuring the efficiency and effectiveness of management in generating profits. Meanwhile, company size is often associated with stability, access to financing, and investor perceptions of risk. Using a qualitative approach, data were obtained through financial report documentation, literature studies, and descriptive analysis of the company's internal conditions. The results of the study indicate that increasing profitability is directly proportional to increasing company value, but company size is not always directly correlated to that value, depending on market perception and operational efficiency. This study recommends that companies must maintain a balance between size growth and profitability effectiveness to keep company value competitive.